Collaboration technologies and social computing : 10th International Conference, CollabTech 2018, Costa de Caparica, Portugal, September 5-7, 2018, Proceedings /: 10th International Conference, CollabTech 2018, Costa de Caparica, Portugal, September 5-7, 2018, Proceedings. (2018) - Unknown
No abstract available